Episode of cervix cancer: Facts and not fantasy - Salgaonkar, Rajshree (International Journal of Nursing Research, 2023)
Cervical cancer is the third most common cancer worldwide, and 80% of cases occur in the developing world. Even with recent advanced technology man is unable to find out exact etiology of cancer. Cancer shows different behavioral pattern. Some cancer can only see in male and some in female. Cancer is autonomous disease which is not particularly limited to age group or etiological factor. Cervical cancer is the one type of cancer which can be seen in female which is ranking 2nd for death of the women globally. Cervical Cancer is malignant carcinoma type of cancer originates in cervix region. The cervix is the narrow portion of the uterus where it joins with the top of the vagina. Most cervical cancers are squamous cell carcinomas, arising in the squamous (flattened) epithelial cells that line the cervix. Adenocarcinoma, arising in glandular epithelial cells is the second most common type. Very rarely, cancer can arise in other types of cells in the cervix. In spite of that in developing countries women are dying with cancer due to lack of knowledge and inadequate medical facilities. In this situation, very little can be expected for commercial sex workers who are one of the most neglected and vulnerable group of the society. It is very necessary for them to know about cancer cervix so that they can be motivated to approach the medical facilities available for them therefore decreasing the morbidity and mortality rate.